Political Mission of University: A Retrospective View - S. G. Lukovenkov (Высшее образование в России)
Academic3 space in its different manifestations has been taking an honorable position in social structure from the earliest stages of the history of human civilization by systematizing multitude experiences of both external and internal world of humankind. At the same time, educational landscape was formulating the different ways of how to theorize about and interact with the world. Simultaneously, there was always combating with the alternative systems and, what is more, this struggle wasn’t necessarily intellectual or polemical. Little has changed in how society perceives academy and its functions in the era of accomplished digital revolution, including its role as an instrument of surveillance and social sorting – these two important elements of power. In this article, an attempt is taken to comprehend University – and speaking broadly academic space as such – as a special kind of social and political field used to perform surveillance and social control. On the example of colonial colleges in the USA, this article examines how University may serve as a surveillance mechanism on the one hand and as a mean of cultural transformation on the other hand, and what conclusions can be made regarding the present and the future of University in the digital era.